DEVELOPMENT OF STEM-BASED TEACHING MATERIALS WITH ENGINEERING DESIGN PROCESS MODEL ON GLOBAL WARMING: VALIDITY ASPECT - Nurul Fitriyah Sulaeman; Septyani Triwulandari; Muliati Syam (JURNAL PEMBELAJARAN FISIKA, 2022)
Development of STEM-based s teaching materials with the Engineering Design Process model on global warming in high school aims to produce valid teaching materials. This research is an earlier stage of development research that uses the ADDIE model research design which consists of five stages, that is Analysis, Design, Development, Implementation, and Evaluation. In this study, the validity aspect was carried out from the analysis, design, and development stages. The teaching materials that have been developed are assessed for product suitability by validators and expert users is five physics education lecturers at Mulawarman University and one teacher at SMA Negeri 5 Samarinda. Based on the results of the validity, the level reached 80.0% that catagorized as valid. Based on the results teaching materials on global warming are suitable to use and continue to implementation and evaluation stages